2020
DOI: 10.3329/bju.v15i2.45917
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on Periprostatic local anesthesia with Intraprostatic local anesthesia for ultrasonoguided transrectal prostatic biopsy

Abstract: Objectives: To compare pain, systemic lidocaine toxicity and complications between periprostatic with intraprostatic local anaesthesia for transrectal prostate biopsy. Methods: This study was carried out in the Department of Urology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka Medical College (DMCH) and Comfort Nursing Home, Dhaka during the period of January 2009 to October 2009, For this purpose, a total number of 60 consecutive patients having increased prostate specific antigen (PSA &g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Improving patient tolerance and comfort associated with the procedure, by decreasing associated pain and morbidity, is therefore of paramount importance. Regarding the complications of biopsy procedure a study showed that rectal bleeding was more than urinary tract infection in their series [28,29,30,31]. In a current study urinary tract infection, hematuria were found less in a group which were given intraprostaic anaesthesia during TRUS [10,32,33,34].…”
Section: Discussionsupporting
confidence: 41%
“…Improving patient tolerance and comfort associated with the procedure, by decreasing associated pain and morbidity, is therefore of paramount importance. Regarding the complications of biopsy procedure a study showed that rectal bleeding was more than urinary tract infection in their series [28,29,30,31]. In a current study urinary tract infection, hematuria were found less in a group which were given intraprostaic anaesthesia during TRUS [10,32,33,34].…”
Section: Discussionsupporting
confidence: 41%
“…They also showed that apical periprostatic nerve block ensured better pain control during transrectal prostate biopsy, compared with endorectal lidocaine gel. One of the most recent studies, reported that intraprostatic local anesthetic injection significantly decreased the pain associated with prostate biopsy, compared with periprostatic nerve blockand found that transperineal unilateral pudendal nerve injection of local anesthetic was effective in reducing the pain at both biopsy and probe manipulation 26,27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Intraprostatic administration of local anesthesia significantly decreases pain during prostate biopsy compared with periprostatic injection. 28,29,30 This review article was carried out with an aim to prefer intraprostatic local anaesthesia for transrectal prostate biopsy. Regarding comparison between intra and periprostatic local anaesthetic measures it was observed that intraprostatic route is more comfortable -24,25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation